Brain‐targeted exosome‐mimetic cell membrane nanovesicles with therapeutic oligonucleotides elicit anti‐tumor effects in glioblastoma animal models - Youngki Lee; Minkyung Kim; Junkyu Ha; Minhyung Lee (Wiley, 2023)
Abstract The brain‐targeted delivery of therapeutic oligonucleotides has been investigated as a new treatment modality for various brain diseases, such as brain tumors. However, delivery efficiency into the brain has been limited due to the blood-brain barrier. In this research, brain‐targeted exosome‐mimetic cell membrane nanovesicles (CMNVs) were designed to enhance the delivery of therapeutic oligonucleotides into the brain. First, CMNVs were produced by extrusion with isolated C6 cell membrane fragments. Then, CMNVs were decorated with cholesterol‐linked T7 peptides as a targeting ligand by hydrophobic interaction, producing T7‐CMNV. T7‐CMNV was in aqueous solution maintained its nanoparticle size for over 21 days. The targeting and delivery effects of T7‐CMNVs were evaluated in an orthotopic glioblastoma animal model. 2'‐O‐metyl and cholesterol‐TEG modified anti‐microRNA‐21 oligonucleotides (AMO21c) were loaded into T7‐CMNVs, and biodistribution experiments indicated that T7‐CMNVs delivered AMO21c more efficiently into the brain than CMNVs, scrambled T7‐CMNVs, lipofectamine, and naked AMO21c after systemic administration. In addition, AMO21c down‐regulated miRNA‐21 (miR‐21) levels in glioblastoma tissue most efficiently in the T7‐CMNVs group. This enhanced suppression of miR‐21 resulted in the up‐regulation of PDCD4 and PTEN. Eventually, brain tumor size was reduced in the T7‐CMNVs group more efficiently than in the other control groups. With stability, low toxicity, and targeting efficiency, T7‐CMNVs may be useful to the development of oligonucleotide therapy for brain tumors.